2005
DOI: 10.1111/j.1553-2712.2005.tb00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Patient Screening across Medical Specialties

Abstract: Using the same instrument and protocol, different rates of IPV and detection of IPV were found across medical departments, with the highest rates in emergency departments and an addiction recovery program. It is especially important for assessment of IPV to include young women who present to medical departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 23 publications
5
65
4
Order By: Relevance
“…First, the low response rate (22%) may indicate a nonresponder bias. Although our response rate is similar to other surveys of IPV among healthcare providers (range, 14%-83%) [8,13,16,19,23,26,28], the data should be interpreted with caution. Second, our results may not be generalizable to practices across the world, as the survey was administered to North American orthopaedic traumatologists only.…”
Section: Discussionmentioning
confidence: 67%
“…First, the low response rate (22%) may indicate a nonresponder bias. Although our response rate is similar to other surveys of IPV among healthcare providers (range, 14%-83%) [8,13,16,19,23,26,28], the data should be interpreted with caution. Second, our results may not be generalizable to practices across the world, as the survey was administered to North American orthopaedic traumatologists only.…”
Section: Discussionmentioning
confidence: 67%
“…The methods and results of this initial phase of the study are reported elsewhere. 28,29 Volunteers were also recruited through posters displayed in public places and health care sites in the Greater Boston area. Initial interviews (Time 1) took place at a secure research facility with trained interviewers in 2003-2004; a subsequent phone interview (Time 2) was conducted an average of 9.5 months later (range 69-782 days).…”
Section: Methodsmentioning
confidence: 99%
“…5 Patients who are victims of IPV frequently visit the emergency department (ED). 6 However, there is little if anything written about children in the homes of those adult victims. 6 The purposes of the present retrospective cohort study were 1) to determine demographics of children in homes where police are called for IPV and 2) to compare the relative risk of perpetrator versus victim in those who, as children, witnessed or were victims of either IPV or sexual assault.…”
mentioning
confidence: 99%
“…6 However, there is little if anything written about children in the homes of those adult victims. 6 The purposes of the present retrospective cohort study were 1) to determine demographics of children in homes where police are called for IPV and 2) to compare the relative risk of perpetrator versus victim in those who, as children, witnessed or were victims of either IPV or sexual assault. We hypothesized that the risk of previous victimization as children would be higher in adult perpetrators of IPV than in adult victims of IPV.…”
mentioning
confidence: 99%